Energy price reform and food markets: the case of bread supply chain in Iran. (29th June 2015) - Mosavi, Seyed Habibollah
Abstract: Reforming energy price is the core of Iranian economic reform plan during 2010–2014. However, increasing price of energy may have adverse effects on the agricultural and food markets. This study was conducted to address these problems in the most important food of Iranian people "bread" by developing a spatial supply chain model. Results show that consumers' welfare would experience a sharp decrease though the impacts on farmers are trivial. Also, results indicate that the key to success the reform without political backlash in the short‐run is the cash transfer program under which the government redistributes part of the reform's benefits among consumers. Per capita compensation payments would be equal to 51.50 and 46.09 US$ per year for a typical rural and urban person, respectively. Moreover, the results provide more detailed information about the market characteristics and the payments both in nationwide and regional scale as well as in different income groups.